2011
DOI: 10.3746/jfn.2011.16.2.174
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Particle Size of Zinc Oxides on Cytotoxicity and Cell Permeability in Caco-2 Cells

Abstract: The cell permeability and cytotoxic effects of different-sized zinc oxide (ZnO) particles were investigated using a human colorectal adenocarcinoma cell line called Caco-2. Morphological observation by scanning electron microscopy revealed that three zinc oxides with different mean particle sizes (ZnO-1, 20 nm; ZnO-2, 90~200 nm; ZnO-3, 1~5 μm) tended to aggregate, particularly in the case of ZnO-1. When cytotoxicities of all three sizes of zinc oxide particles were measured at concentration ranges of 1~1000 μg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…This finding is consistent with various in vivo and in vitro studies concerning HTs, tannic acid, and other polyphenolic compounds [20,49,50]. Conversely, existing literature on ZnO primarily focuses on nanoparticle formulations, which may induce increased cellular cytotoxicity [51]. However, zinc deficiency is linked to compromised selective intestinal permeability, observed in conditions like Crohn's disease and ulcerative colitis, marked by structural and functional alterations of ZO-1 and OCLN [52].…”
Section: Discussionsupporting
confidence: 84%
“…This finding is consistent with various in vivo and in vitro studies concerning HTs, tannic acid, and other polyphenolic compounds [20,49,50]. Conversely, existing literature on ZnO primarily focuses on nanoparticle formulations, which may induce increased cellular cytotoxicity [51]. However, zinc deficiency is linked to compromised selective intestinal permeability, observed in conditions like Crohn's disease and ulcerative colitis, marked by structural and functional alterations of ZO-1 and OCLN [52].…”
Section: Discussionsupporting
confidence: 84%
“…For example, translocation across the intestinal barrier and cytotoxic effects of a panel of zinc oxide (ZnO) NMs (of various sizes) has been studied using differentiated Caco-2 cells. It was observed that ZnO NMs (20 nm) had a higher level of permeation across the intestinal barrier and elicited greater cytotoxicity than larger particles (diameter of 1–5 μm or 90–200 nm) [ 60 ], demonstrating that particle translocation across the intestinal barrier may be a size dependent phenomenon. There is also evidence that gold NMs (1.4 to 200 nm) can translocate across the intestinal barrier of rats following ingestion [ 61 ].…”
Section: Introductionmentioning
confidence: 99%
“…This finding is consistent with various in vivo and in vitro studies concerning HTs, tannic acid, and other polyphenolic compounds [ 20 , 51 , 52 ]. Conversely, the existing literature on ZnO primarily focuses on nanoparticle formulations, which may induce increased cellular cytotoxicity [ 53 ]. However, zinc deficiency is linked to compromised selective intestinal permeability, which is observed in conditions like Crohn’s disease and ulcerative colitis, marked by structural and functional alterations of ZO-1 and OCLN [ 54 ].…”
Section: Discussionmentioning
confidence: 99%